Leadership Effect on Improving Learning in Producing Cooperatives of Tehran City - M Nourbakhsh; S.S Tavakoli (تعاون و کشاورزی, 2010)
In this age organizations rate of learning should be faster than environment rate of changing if they hope to survive. This shows the importance of individual and organizational learning. Cooperatives akin to other organizations should consider this fact in order to play their key role in the economy of the country. This study examines the role of leadership in improving learning in Tehran’s producing cooperatives. The study was carried out in 2010 and the data used in the analysis were derived from questionnaires distributed in 5 cooperatives in Tehran which were taken from the population of active producing cooperatives with random sampling methods and then the number of respondents was selected through Cochran formula. Correlation – Regression analysis was used in order to test research hypotheses. The results showed that leadership can improve and develop learning (individual & organizational learning) in these cooperatives, therefore cooperatives can facilitate this process by consideration of the experience of the candidates for the board of directors and managing director, identifying creative and innovative members and supporting them, supporting productive ideas and suggestions, dispatching members to obtain necessary skills and qualification, determining the cooperatives vision and effective planning and monitoring.